Vladimir Solovyov’s Latin outline in Fedor Dostoevsky’s “The Writer’s Diary”: a scholarly myth or a literary fact - Alexander Rychkov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The paper focuses on a hypothesis (so far unproved) that in the Writer’s Diary (May-June 1877) F.M. Dostoevsky published a Latin extract from Johannes Lichtenberger’s Prognosticatio, he got from Vladimir Solovyev who made this extract while staying in London in 1875. To clarify the point, V. Solovyov’s extract "1528. Liechtenberger” taken from Lichtenberger’s edition is published herewith and introduced into scientific use. One can see that Solovyov used several abbreviations and compilations that are fully and exactly reproduced in the Writer’s Diary; it proves the fact that Solovyov’s Latin extract was the source for Dostoevsky. The paper analyses religious, philosophical, and prophetic context behind Lichtenberger’s fragments that attracted Russian thinkers in connection with speculations on the future of Christianity and Russia. One can trace in Solovyov’s philosophical heritage the echo of his encounter with Dostoevsky devoted to the interpretation of the prophesies; a special attention is paid to A Short Tale of the Antichrist. Solovyov’s Latin extract can be considered in relation to the theory of three ages by Joachim of Fiore and the Joachimite tradition, that was a basis both for Lichtenberger and Solovyov’s of Trinitarian historiosophy and metaphysics. The paper concludes with the analysis of a poetic fragment, created by Solovyov during his trip to London and comprising his first “intuitions of Sophia”, in connection with the problems under consideration. A vast bibliography is attached.